Relações filogenéticas das espécies da família Callichthyidae : (Ostariophysi, Siluriformes) - Vera-alcaraz, Héctor Samuel (2013)
The phylogeny of the family Callichthyidae (Siluriformes) was investigated performing a Cladistic parsimony analysis under a Total Evidence approach. Characters explored are mainly based in osteology and molecular data of nuclear and mitochondrial genes. The ingroup included 131 terminals representing 111 species, the outgroup included 13 terminals representing 13 species including Copionodon as the rooting taxa. The phylogenetic analysis resulted in 89 most parsimonious trees which are summarized in a strict consensus cladogram; a new phylogenetic classification and the discussion of this paper are addressed based in this topology. The Total Evidence phylogenetic analysis corroborated the monophyly of the family Callichthyidae, subfamilies Callichthyinae and Corydoradinae, genera Callichthys, Dianema, Lepthoplosternum, Megalechis, and Scleromystax. However, the genera Aspidoras, Corydoras, and Hoplosternum are recovered nonmonophyletic. To reconcile this situation, a revalidation of the genera Hoplisoma and Gastrodermus is proposed to accommodate most species currently recognized in Corydoras. Aspidoras virgulatus and Corydoras lacerdai are transferred to Scleromystax to conceive their currently containing genera monophyletic. On the other hand, Hoplosternum is recovered paraphyletic. However, it was decided to hold making taxonomic changes at this moment until molecular dataset is completed for this genus, which is referred temporarily as Hoplosternum . Synapomorphies for each clade recovered and ranked in the phylogenetic classification are reported here, emphasizing their morphological diagnoses. Interrelationships between species and clades are discussed and compared with previous taxonomic and phylogenetic hypotheses. In addition, the taxonomy of Hoplisoma nattereri was reviewed in order to elucidate its synonymy and investigate the presence of cryptic diversity under this name. Hoplisoma nattereri and H. triseriatus are considered valid species. Geographic distribution for each species is also reported. Corydoras juquiaae is removed from the synonymy of Hoplisoma nattereri and transferred to Scleromystax juquiaae, new combination. Scleromystax prionotos is considered a junior synonym of S. juquiaae. All these species are illustrated in this paper. In addition, the original figure of S. juquiaae prepared but never published by Rudolph von Ihering is reproduced here. Phylogenetic relationships of Hoplisoma nattereri and H. triseriatus are discussed and also the morphometric and genetic distance of some of the populations sampled.